(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
In India, the life insurance industry has seen significant development in recent years. Insurance services are undergoing a transformation, and the industry’s openness has posed many serious risks and difficulties to Life Insurance Corporation of India (LIC), the country’s sole public sector life insurance service provider. People are worried about their own and their loved one’s futures. Life insurance provides assistance to a deserving recipient at a difficult period. Life insurance firms, on the other hand, are in fierce rivalry. Players in the life insurance industry have begun to recognize that customer service and satisfaction are critical to their success. As a result, a proactive approach to client satisfaction should be taken. The effect of demographic variables on customer satisfaction with Life Insurance Company is investigated in this research. It was shown that most policyholders consider their life insurance company to be safe and reliable. It is recommended that a life insurance company offer timely and accurate information to current clients in order for them to remain loyal and promote good word of mouth about them.